What Do Words Do for Us?. (13th December 2017) - Cann, Ronnie; Kempson, Ruth
Abstract: In this paper we adopt the hypothesis that languages are mechanisms for interaction, and that grammars encode the means by which such interaction may take place, by use of procedures that construct representations of meaning from strings of words uttered in context, and conversely strings of words are built up from representations of content in interaction with context. In a review of the systemic use of ellipsis in dialogue and associated split‐utterance phenomena, we show how, in Dynamic Syntax, words give rise to a range of procedures for the building of representations of the content of some utterance, which both speakers and hearers use. We then extend the discussion to take account of adjuncts, showing how they contribute to content construction both in single utterances and across speakers. The same mechanisms are then shown to underlie the building of inferential extensions of meaning in context, giving rise to the creation of the ad hoc concepts expressed by phrases or single words in relation to the utterance context and ultimately to the creation of metaphorical uses of language.